A comparative prospective study of maternofetal outcome in advanced and younger maternal age group in higher socioeconomic strata - Rehman, Bilal ur; Sirwal, Rabia Khurshid; Wani, Feroz Ahmad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal age in pregnancy is increasing over the world and has been widely documented. Nowadays many women delay their pregnancy even up to the 40th year of life because of different reasons like changing social and economic trend. Simultaneously higher advanced technique and better supported maternal and neonatal care also exist. Methods: To have an idea of balance between advanced age and advanced support this comparative prospective study was done on 40 advanced and 40 younger maternal age groups to compare the pregnancy outcomes. To find out the association Chi-Square and unpaired ‘t’ test was used. Results: It was observed in this study that Assisted reproductive techniques (mode of conception) and cesarean section rates were significantly higher in advanced maternal age. Although there were no significant differences in antenatal and postpartum complications between the two groups. Conclusions: It can be concluded that if a women with advanced maternal age is cared at a hospital with advanced techniques, the adverse pregnancy outcomes will not be different from the non-elderly women.